Urban Environment, Travel Behavior, Health, and Resident Satisfaction - Antipova, Anzhelika (Springer International Publishing, 2018)
This book explores the intersections of urban development, travel patterns, and health. Currently, there is a lack of research concerning the subjective dimensions of accessibility in urban environments and travel behavior, as well as travel-related outcomes. Antipova fills this gap in the scholarship by developing an analysis of satisfaction and perception-related indicators at an intraurban level. Specifically, she investigates various aspects of urban environment from the perspective of resident perception and satisfaction, as well as the relationship between urban environment, travel behavior, activity patterns, and traveler health.